Familial DNA searching- an emerging forensic investigative tool. Issue 1 (January 2019) - Debus-Sherrill, Sara; Field, Michael B.
Abstract: In recent years, jurisdictions across the United States have expressed a growing interest in aiding criminal investigations through the use of familial DNA searching (FDS)- a forensic technique to identify family members through DNA databases. The National Survey of CODIS Laboratories surveyed U.S. CODIS laboratories about their perceptions, policies, and practices related to FDS. In total, 103 crime labs completed the survey (77% response rate). Labs in 11 states reported using FDS, while labs in 24 states reported using a similar-but distinct- practice of partial matching. Although the majority of labs had positive perceptions about the ability of FDS to assist investigations, labs also reported a number of concerns and challenges with implementing FDS. Respondents reported using either practice a limited amount with modest numbers of convictions resulting from both FDS and partial matching. The article reports on varying practices related to official policies, training, eligibility, the software search, lineage testing, requirements for releasing information, and subsequent investigative work. Finally, the article discusses what can be learned from this survey, accompanying limitations, and implications for decision-makers considering using FDS. Highlights: Perceptions of FDS are mostly positive, although labs continue to have concerns. There is sizable interest in the tool from labs not currently performing FDS. Labs commonly (but not universally) had publicly available policies and training. FDS typically has more restrictions and protections compared to partial matching.